A molecular toxicological study to explore potential health risks associated with ultrafine particle exposure in cold and humid indoor environments - Ziyu Shu; Shuo Qing; Xu Yang; Ping Ma; Yang Wu; Baizhan Li; Fangxin Fang; Runming Yao (Ecotoxicology and Environmental Safety)
Environmental pollutants including ultrafine particulate matter (UFPs) and adverse meteorological conditions pose significant public health impacts, particularly affecting respiratory health. This study aims to elucidate the synergistic effects of cold-humid conditions and UFPs exposure on respiratory health, utilizing Carbon Black Nanoparticles (CB-NPs) as surrogates for UFPs. Through comprehensive lung function tests, histopathological examinations, and biomarker analyses, this research focuses on the modulation of oxidative stress signaling pathways and NF-κB activation. Male Balb/c mice were exposed to specific concentrations of CB-NPs (30–50 nm in diameter, 0.184 mg/(kg·day)) in a controlled environmental chamber mimicking cold (10°C/14°C) and humid (90 % RH) conditions over three weeks. The results indicate that exposure to CB-NPs alone increased lung function, oxidative stress (ROS, GSH, MDA), inflammation (IL-6, TNF-α, IL-1β), apoptosis (Caspase 3, Caspase 8, Caspase 9), and histopathological alterations in lung tissue. Furthermore, these effects were notably more severe under combined exposure with cold-humid conditions. These results suggest that the adverse effects of pollutants are not solely concentration-dependent but are exacerbated by specific environmental contexts. It is evident that Vitamin E (100 mg/kg/day) can attenuate these adverse effects, underscoring its potential as a protective agent against environmental stressor-induced air pollutants and cold humid conditions. Our findings suggest that the synergistic effects of environmental factors and pollutant exposure significantly impact respiratory health, providing valuable insights for the design of healthier indoor environments and the development of strategies to mitigate these risks.